Partially coupled extended stochastic gradient algorithm for nonlinear multivariable output error moving average systems. Issue 2 (18th April 2017) - Wang, Xuehai; Ding, Feng
Abstract : Purpose: The purpose of this paper is to study the parameter estimation problem of nonlinear multivariable output error moving average systems. Design/methodology/approach: A partially coupled extended stochastic gradient algorithm is presented for nonlinear multivariable systems by using the decomposition technique. Findings: The proposed algorithm can realize the coupled computation of the parameter estimates between subsystems. Originality/value: This paper develops a coupled parameter estimation algorithm for nonlinear multivariable systems and directly estimates the system parameters without over-parameterization.